Assessing the performance of LTE and NLTE synthetic stellar spectra in a machine learning framework. Issue 3 (26th August 2020) - Bialek, Spencer; Fabbro, Sébastien; Venn, Kim A; Kumar, Nripesh; O'Briain, Teaghan; Yi, Kwang Moo
ABSTRACT: In the current era of stellar spectroscopic surveys, synthetic spectral libraries are the basis for the derivation of stellar parameters and chemical abundances. In this paper, we compare the stellar parameters determined using five popular synthetic spectral grids (INTRIGOSS, FERRE, AMBRE, PHOENIX, and MPIA/1DNLTE) with our convolutional neural network (CNN, StarNet ). The stellar parameters are determined for six physical properties (effective temperature, surface gravity, metallicity, [ α /Fe], radial velocity, and rotational velocity) given the spectral resolution, signal-to-noise ratio, and wavelength range of optical FLAMES-UVES spectra from the Gaia-ESO Survey. Both CNN modelling and epistemic uncertainties are incorporated through training an ensemble of networks. StarNet training was also adapted to mitigate differences between the synthetic grids and observed spectra by augmenting with realistic observational signatures (i.e. resolution matching, wavelength sampling, Gaussian noise, zeroing flux values, rotational and radial velocities, continuum removal, and masking telluric regions). Using the FLAMES-UVES spectra for FGK-type dwarfs and giants as a test set, we quantify the accuracy and precision of the stellar label predictions from StarNet . We find excellent results over a wide range of parameters when StarNet is trained on the MPIA/1DNLTE synthetic grid, and acceptable results over smaller parameter ranges when trained on the 1DLTE grids. These tests also show that our CNN pipeline is highly adaptable to multiple simulation grids.